The implementation of code blue by nurses as first responders in outpatient and inpatient rooms at Malang Indonesia Hospital - Tony Suharsono; Sunarmi Sunarmi; Nur Ida; Bella Nove Khirria; Nazla Asrin; Ikhda Ulya (PAGEPress Publications, 2023)
Introduction: In-Hospital Cardiac Arrest (IHCA) is a frequent occurrence that necessitates prompt and appropriate assistance to improve survival rates. Nurses in public care rooms and outpatients are expected to be first responders to IHCA until an activated hospital code blue team arrives. Therefore, this study aims to analyze the implementation of code blue response by nurses in outpatient and hospital inpatient rooms in Malang. Design and Methods: This is a quantitative study that uses observational methods with a cross-sectional approach comprising of 109 inpatient and outpatient care room nurses from 9 hospitals in Malang. The implementation of code blue was measured by a simulated case of adult cardiac arrest in a hospital inpatient room. Results: The nurses involved were 67.0% female, where the majority have a D3 education qualification (57.7%), with more than ten years working experience (45%). Furthermore, 83.5% of nurses work in regular care rooms and 16.5% come from outpatient rooms. The results showed that the implementation of code blue by nurses in regular care and inpatient rooms was 66.7% and 65.9%, respectively in the insufficient categories. In addition, the Mann-Whitney U test obtained a p-value of 0.929. Conclusions: In conclusion, there was no significant difference in the implementation of code blue that occurred in the inpatient and outpatient rooms. Further studies were recommended to observe code blue events directly and take samples with balanced proportions.